Techniques of financial analysis : a guide to value creation - Helfert, Erich A. (Boston : McGraw-Hill / Irwin, 2003)
Business
2003-04-21
Keywords: Finance; Corporation-Finance; Financial management; Cash flow; Financial statements; Ratio analysis; Investment